2018
DOI: 10.1089/mdr.2017.0057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Carbapenem-Resistant Acinetobacter baumannii in a Tertiary Care Hospital in Egypt: Clonal Spread of blaOXA-23

Abstract: Of great concern is the increased frequency of carbapenem-resistant Acinetobacter baumannii (CRAB) causing healthcare-associated infections. Different classes of β-lactamases are involved in this resistance through hydrolyzing carbapenems. Multilocus sequence typing (MLST) has been applied successfully for characterizing different varieties of bacterial pathogens epidemiologically. In the present study, we aimed to type and characterize the resistance profile of clinical isolates of CRAB causing healthcare-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
4
13
4
Order By: Relevance
“…ST585 is the single loci variant (SLV) of ST391, which was first reported in India by Rynga et al [56]. Another study from Egypt showed that the study isolates belonging to ST391 carries bla OXA-23 alone or bla NDM alone or bla OXA-23 with bla KPC , which is in contrast to the current study where CIAT758 belongs to ST589 and carries bla OXA-23 with bla OXA-58 [36]. Such findings indicate that despite diverse sequence types, bla OXA-23 is the major contributor of carbapenem resistance in A. baumannii worldwide.…”
Section: Multi-locus Sequence Typing (Mlst)contrasting
confidence: 84%
See 2 more Smart Citations
“…ST585 is the single loci variant (SLV) of ST391, which was first reported in India by Rynga et al [56]. Another study from Egypt showed that the study isolates belonging to ST391 carries bla OXA-23 alone or bla NDM alone or bla OXA-23 with bla KPC , which is in contrast to the current study where CIAT758 belongs to ST589 and carries bla OXA-23 with bla OXA-58 [36]. Such findings indicate that despite diverse sequence types, bla OXA-23 is the major contributor of carbapenem resistance in A. baumannii worldwide.…”
Section: Multi-locus Sequence Typing (Mlst)contrasting
confidence: 84%
“…Presence of bla OXA-23 and bla OXA-58 in six CRAB isolates was previously reported by Principe et al [35]. El Bannah et al reported that 86 % of carbapenem resistance could be due to the presence of either bla OXA-23 alone or bla OXA-23 together with bla KPC [36]. However, in this study bla OXA-23, bla OXA-58 and bla NDM-1 was present, but bla KPC was not observed.…”
Section: Resistance Determinantssupporting
confidence: 51%
See 1 more Smart Citation
“…The noticeable prevalence of bla OXA-23 -carrying Acinetobacter in Egypt is a crucial health-care concern that necessitates strict interventions to eliminate such infections [13] , [12] . Neither bla OXA-24 nor bla OXA-58 was found among the tested isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the bla OXA-23 gene existed in most CRAB isolates but was absent for most CSAB isolates, which indicated that bla OXA-23 was the major mechanism for carbapenem resistance of CRAB isolated from CSF and blood. The bla OXA-23 gene was also the most important mechanism for carbapenem resistance in CRAB in China [18,23] and some other countries [24][25][26]. On the other hand, the bla OXA-24 gene was another mechanism for carbapenem resistance, as bla OXA-24 -positive but bla OXA-23 -negative isolates in this study showed meropenem-resistance and imipenem-sensitive characteristics.…”
Section: Discussionmentioning
confidence: 46%